Evaluasi Konteks Dalam Penerapan Kurikulum dan Pembelajaran Berbasis Part 66/147 European Aviation Safety Agency di Politeknik Penerbangan - Wira Gauthama; Lilies Esthi Riyanti (Politeknik Penerbangan Indonesia Curug, 2022)
This study is primarily based on the need for an appropriate implementation of curriculum and learning in the Direct European Aviation Safety Agency (EASA) Part 66/147 program adopted in Prodi TPU of Politeknik Penerbangan Indonesia Curug commenced in 2020. A tangible difference in the curriculum’s structure and learning between EASA 66/147 standards and the National Curriculum Standard was expected as the cause of why the process and learning objectives of the EASA Second Site 2013 – 2018 program were not achieved, as shown in the measured internal audit report and examination results throughout the periods. The fundamental discrepancies were identified as the subject modularization, practical assessment methods, learning hours for each subject, and total learning duration for similar learning objectives as CASR 147 standards implemented in Prodi TPU. EASA 66/147’s curriculum and learning standard were implemented in the previous Second Site program by inserting the EASA part 66 syllabus into the similar subject in Prodi TPU’s curriculum and had been implemented for the study program of D III TPU batch 12th, 13th and 14th. The examination results for all modules were evaluated as not satisfactory dan failed to achieve the target according to the average result of the first examination showed that 81% of participants failed to pass. The assumption made it resulted from an inappropriate adoption of EASA part 66/147’s curriculum into the existing learning process and methods been utilizing in Prodi TPU so that emerging the needs of the curriculum to be reconstructed with the accepted pattern before the next EASA program’s implementation to have good learning impact which suited with EASA, AMTO and National standard. As the research tools, context evaluation (part of the CIPP method: Context, Input, Process, and Product) initiated by Stufflebeam, Daniel F (2000, p.282) is utilized as it can be empowered to be an evaluation instrument in the various education area. Research data was collected from internal audit results, EASA examination results, related document review, and interviews with instructors and participants who were involved in the Seconsite program, and then compared with data collected from other Polytechnics under PPSDMPU with AMTO 147 program Data resulting from each phase of CIPP evaluation was analyzed quantitatively and qualitatively by Mixed Method Research (Creswell dan Clark, 2000) utilizing combined concurrent triangulation to have a comprehensive and intact view of cause and solution. The finding resulting from context evaluation shows the need for specialized knowledge and experience in developing programs for teachers, learning facilities that have experienced downgrades, the composition of theory and practice in the curriculum, learning needs of cadets, global market needs and domestic regulations, internal stakeholder support, depth and breadth of study materials and reference books. All the findings are important aspects for the basis of reconstructing an emerging curriculum which more adoptable with the existing learning environment and accommodates all standards needed by EASA part 66/147, CASR 147, and the National Standard of Education